(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tobacco usage in the form of smoking or chewing has increased the risk of oral potentially malignant disorders (OPMDs) and oral cancer. These deleterious habits are also related to changes in dentition and the oral mucosa. Aim: The aim of our study was to evaluate the oral changes associated with tobacco usage among residents of rural Kanpur. Materials and methods: This study was conducted among the residents of rural Kanpur, Uttar Pradesh, India, using stratified cluster random sampling, prestructured questionnaires, and detailed oral examination. A total of 250 patients with a previous history of tobacco usage were enrolled in this study after obtaining informed consent. Age- and gender-matched controls were also evaluated to correlate the findings. Clinical details were documented, including the Oral Hygiene Index-Simplified (OHI-S), Decayed-Missing-Filled Teeth (DMFT) index, Community Periodontal Index (CPI), loss of attachment, dental findings, and oral mucosal changes. Suspicious lesions were stained with toluidine blue, and a biopsy was performed for histopathological evaluation. The tabulated results were statistically analyzed using the Statistical Package for the Social Sciences (SPSS) version 21.0 (IBM SPSS Statistics, Armonk, NY, USA) for significance. Results: Attrition, abrasion, and erosion of teeth were more frequent in tobacco users than in controls. Smoker’s palate, tobacco pouch keratosis, and leukoplakia were commonly noted mucosal lesions. The mean values of the parameters of the DMFT score (3.560), CPI score (2.190), and loss of attachment score (0.542) were higher among tobacco users, and it was statistically significant (P value < 0.05). Out of 250 patients, 42 had suspicious lesions. It included seven cases of oral submucous fibrosis (OSMF), two cases of tobacco pouch keratosis, and eight cases of leukoplakia. Toluidine blue staining and biopsy were performed. Histopathological examination of suspicious lesions revealed hyperkeratosis, various grades of epithelial dysplasia, and differing inflammatory responses. Out of 42 biopsied cases, there were two cases of hyperkeratosis with severe epithelial dysplasia, four cases of hyperkeratosis with moderate epithelial dysplasia, two cases of hyperkeratosis with mild dysplasia, two cases of superficially invasive squamous cell carcinoma, five cases of advanced OSMF, and two cases of moderately advanced OSMF. Conclusion: Tobacco usage produces visible changes in dentition and latent alterations in the oral mucosa. Suspicious lesions should always be referred for histopathological examination to identify oral potentially malignant disorders and oral cancer so that prompt treatment could be initiated. Patient education is mandatory to avoid the usage of tobacco in any form